Comparison and Analysis of the Joint Mapping Results in the Sarcheshme and Sungun Porphyry Copper Mines, Iran - Parsaei, M.; Shahriar, K.; Sharifzadeh, Mostafa; Moarefvand, P. (Amirkabir University, 2008)
In this paper, joints mapping methods in general and joint mapping in Sarcheshme and Sungun porphyry copper mines by the Scanline common method, with the aim of field rock mass engineering classification, and the study of the joints hydraulic properties with the respect to groundwater, accompanied by the result of these data statistical processing, and comparison of the results in two mines, are presented. In the western wall of the Sarcheshme copper mine limit, there are two main joint sets with Northwest-Southeast (Set1: Dip/Dip dir.: 46°/082°) and Northeast-Southwest (Set2: Dip/Dip dir.: 80°/051° ) strikes with 3.5mm aperture and infilling materials of clay and pyrite, and in the Sungun copper mine, two main joint sets with Northeast-Southwest (Set1: Dip/Dip dir.: 63o/165o) and Northwest-Southeast (Set2: Dip/Dip dir.: 70°/227° ) strikes with 6mm aperture and infilling materials of clay and iron oxide. In both of mines, joints were recognized with rough and slightly weathered surfaces, damp, with 10-20m persistence and 1m mean spacing. So with comparison and analysis of the results in these two mines, it is observed that in spite of the geographical slightly large distance and especially very different apparent condition of these two mines walls, the joints geomechanic parameters of their rock masses, are very similar and even, in many cases, the frequency percent of them in done statistical study are very near and so the obtained results are very noticeable and useful.